The great African land grab? : agricultural investments and the global food system - Cotula, Lorenzo; International African Institute; Royal African Society; World Peace Foundation (2013)
Large-scale land acquisitions have become one of the most talked about and contentious topics amongst those studying, working in or writing about Africa. Some have welcomed this trend as a bearer of new livelihood opportunities. Others have countered by pointing to negative social impacts. Lorenzo Cotula casts a critical eye over the most reliable evidence on this hotly contested topic, examining the implications of land deals in Africa both for its people and for world agriculture and food security.
Introduction -- Historical roots of the land rush -- Scale, geography and drivers of the land rush -- 'Land grabbing' in the shadow of the law -- Winners and losers -- Conclusion.
Includes bibliographical references (pages 193-228) and index.
Keywords: Land tenure -- Africa; Land use, Rural -- Africa -- History -- 21st century; Agriculture and state -- Africa; Agriculture -- Economic aspects -- Africa; Real property -- Africa; Investments, Foreign -- Africa; Food supply -- Africa; Landnahme; Agrobusiness; Lebensmittelindustrie; Sol, Utilisation agricole du -- Afrique -- Histoire; Accaparement des terres -- Afrique; Afrika